Conciliation vie familiale et vie professionnelle par les femmes travaillant dans le secteur public de la santé à Lomé : quelles stratégies d’adaptation ? - Bilampoa, Gnoumou Thiombiano; Sitsopé, Toudeka Ayawavi; David, Jean Simon (Interventions Économiques, 2021)
Cet article cerne les difficultés, les défis et les stratégies mises en œuvre par les femmes soignantes à Lomé (Togo) dans la conciliation travail-famille. Les données qualitatives ont été collectées auprès de femmes soignantes dans deux formations sanitaires publiques, de leur conjoint et de leurs collègues hommes. Les résultats montrent que les normes et les pratiques culturelles ont confiné les hommes et les femmes dans leurs rôles respectifs selon la division sexuelle du travail. Ainsi, exercer des tâches domestiques est considéré comme un devoir pour les femmes, mais une transgression des normes sociales pour les hommes. Les exigences et les conditions de la profession médicale et l’insuffisance de personnels de santé rendent difficile la conciliation travail-famille pour les femmes. Pour concilier leur vie familiale et professionnelle, les femmes soignantes mettent en œuvre plusieurs stratégies d’adaptation : recours à l’aide parentale, emploi de domestiques et de répétiteurs scolaires, acquisition d’appareils électroménagers.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; care; conciliation famille-travail; famille; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques; togo; travail; travail domestique; travail du care

Hidden in plain sight: Gender analysis of the environmental and social impact assessment of the East African crude oil pipeline - Hill, Christina; Namara, Charité; Orcaya, Jane; Bogrand, André; Sellwood, Scott A. (Impact Assessment and Project Appraisal, 2021)
Large-scale mining, oil, and gas projects can have a profound and negative affect on women’s rights and gender equality. Adverse impacts include the disruption of family and social life; the increased risks to health and safety, especially in terms of domestic and sexual violence; environmental degradation; as well as changing access to and control over land and livelihoods. These adverse impacts fall most heavily on women. This case study focused on the East African Crude Oil Pipeline (EACOP). It shows that conventional environmental and social impact assessment (ESIA) processes may not identify all potential adverse impacts on women, and can fail to analyse the implications of potential impacts on gender norms and gender power relations, leading to a downplaying of the significance of these impacts. The implications for women and girls’ health and safety resulting from the in-migration of large numbers of mostly men seeking project employment and other opportunities and increases in women’s unpaid care work are two potential adverse impacts the EACOP ESIA failed to identify. Strengthening gender analysis within the current suite of impact assessment tools and methodologies, particularly for extractive industries projects, is therefore urgently needed. © 2021 IAIA.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; environnement; extractivisme; industrie pétrolière; ouganda; patriarcat; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; santé des femmes*; systèmes d'oppressions; thématiques; violences

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques